Model Pembelajaran Kesenian di PAUD Ya Ummi Fat Desa Bermi Kecamatan Mijen Kabupaten Demak (Studi Analisis Kurikulum Kesenian untuk Prodi PGRA STAIN Kudus) - Sophya, Ida Vera (THUFULA, 2015)
The process of learning in early childhood should be done with the aim of providing the basic concepts that has significance for children, namelythrough real experience that allows the child to demonstrate the activity and curiosity (curiosity). To achieve this goals, teachers have a position to put his role as a companion, mentor, fasilltator and motivator for their children. This is done to balance the teacher’s roles and parenting who are too dominant to be more democratic so that children have the freedom to explore the world around them. PGRA department as an institution which printers prospective teachers of RA / TK must provide the basics of science and learning models, especially the learning associated with the arts as an asset child to learn comfortably. This is based on the principle that early childhood learning should be delivered by way of playing and singing.